Simulasi Teknologi Jembatan Otomatis pada Jalur Kapal Laut Dengan Mikrokontroler ATmega 8: Simulation of Automatic Bridge Technology on Marine Ship Lines With ATmega 8 . Microcontroller - Egi Affandi; H Kusnadi; Amrullah; I U Pradifta (Cered Indonesia Institute, 2022)
The bridge is a construction that is useful for continuing the path through a lower obstacle. Bridges which are part of the road are indispensable in the land transportation network system that will support development in the area. The way this tool works is to initialize the input from the photodiode sensor which detects the presence or absence of a ship. If the 1st sensor detects a ship then the light will be green then if the 2nd sensor detects a ship then the light will be red and the bridge will go up. then if the 3rd sensor is green then the bridge will go down. The result of this automatic bridge tool is that the bridge will open when the ship is detected by sensor 2 and will be closed when the ship detects the 3rd sensor. Keywords: bridge, microcontroller, photodiode, LED.